Anesthesia For Fetoscopic Fetal Surgery: Reverse Arterial Of Perfusion Sequence In Twin Pregnancy - Calderón-Lozano, Marjorie Lisseth (2017)
Introduction. In twin pregnancies with a diagnosis of Reversed Arterial Perfusion (TRAP), sequence, is highly recommendedto be managed by fetoscopic fetal surgery through bipolar photocoagulation, in order to improve the prognosis of oneof the fetuses (pump fetus), in contrast of the other one which is acardiac and/or anencephalic. In this regards anesthesiamanagement has to ensure maternal and fetal safety and provide excellent surgical conditions. Objective. To describe theanesthetic management of a patient diagnosed with TRAP sequence scheduled for bipolar fetoscopic-photocoagulation.